2020
DOI: 10.3390/cells9020497
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome and Translational Control in Stem Cells

Abstract: Embryonic stem cells (ESCs) and adult stem cells (ASCs) possess the remarkable capacity to self-renew while remaining poised to differentiate into multiple progenies in the context of a rapidly developing embryo or in steady-state tissues, respectively. This ability is controlled by complex genetic programs, which are dynamically orchestrated at different steps of gene expression, including chromatin remodeling, mRNA transcription, processing, and stability. In addition to maintaining stem cell homeostasis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 161 publications
(280 reference statements)
9
94
0
Order By: Relevance
“…While this central dogma has been established over the last 60 years, the non-linearity between the levels of a given mRNA and the amount of protein it encodes has only recently started to emerge (5)(6)(7)(8). One explanation for this poor correlation resides in the spatial control of translation that could lead to differential protein output.…”
Section: Introductionmentioning
confidence: 99%
“…While this central dogma has been established over the last 60 years, the non-linearity between the levels of a given mRNA and the amount of protein it encodes has only recently started to emerge (5)(6)(7)(8). One explanation for this poor correlation resides in the spatial control of translation that could lead to differential protein output.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation in mammalian pluripotent cells such as ESCs are shown to involve changes in the gene expression profile, remodeling of organelles and their metabolic states (Dixon et al, 2015;Folmes et al, 2012;Gabut et al, 2020;Sampath et al, 2008). Further, it has been shown that during differentiation, ESCs exhibit increased mitochondrial fusion and a concurrent switch in their metabolic state from glycolytic to oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that there may be tissue-specific dependence on different components of the synthesis and secretory systems, tailored to the unique needs of each tissue. In development, certain ribosome biogenesis factors -which are crucial to ribosomal complex assembly -are specifically expressed in stem cells, and cellular ribosomal content is thought to change as select ribosomes are recruited depending on cell fate (Gabut et al, 2020).…”
Section: Protein Synthesis and Cell-type Specificitymentioning
confidence: 99%